2018
DOI: 10.1016/j.foreco.2018.06.043
|View full text |Cite
|
Sign up to set email alerts
|

The impact of spatial isolation and local habitat conditions on colonization of recent forest stands by ectomycorrhizal fungi

Abstract: Successful colonization of empty habitat patches depends both on the capacity of a species to reach the patch and its ability to establish and persist. Getting better insights into the various factors that affect colonization success is especially relevant in the context of restoration projects that aim at restoring biodiversity in newly created habitats like afforestation. While it is generally known that soil microbial communities play a key role in forest ecosystems, it remains largely unknown how they reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 81 publications
(85 reference statements)
0
19
0
2
Order By: Relevance
“…Fine-scale analyses of the correlation between genotypic similarity and geographic distance in several Russula species found limited gene flow via spore dispersal (Wang et al, 2015). In a study on EcM fungal communities in recent oak stands that were either isolated from or connected to ancient forest, Russula was more abundant in recent stands connected to ancient forest than in isolated stands (Boeraeve et al, 2018), suggesting that Russula species are unable to travel large distances across a hostile landscape matrix. Indicator species analysis on the four age classes revealed a similar pattern with indicator OTUs of the youngest age class belonging to Cenococcum, Tomentella and Sebacina, all known to be efficient dispersers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine-scale analyses of the correlation between genotypic similarity and geographic distance in several Russula species found limited gene flow via spore dispersal (Wang et al, 2015). In a study on EcM fungal communities in recent oak stands that were either isolated from or connected to ancient forest, Russula was more abundant in recent stands connected to ancient forest than in isolated stands (Boeraeve et al, 2018), suggesting that Russula species are unable to travel large distances across a hostile landscape matrix. Indicator species analysis on the four age classes revealed a similar pattern with indicator OTUs of the youngest age class belonging to Cenococcum, Tomentella and Sebacina, all known to be efficient dispersers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that, although these root-associated symbionts show large differences in dispersal capacity, even highly dispersive species show rapidly decreasing spore loads with increasing distance from source patches (Peay et al, 2012). As a consequence, EcM fungal communities in newly established habitats may be highly affected by dispersal limitation (Peay et al, 2010) and it is therefore not unlikely that spatial isolation and overall landscape connectivity contribute to EcM fungal community assembly (Peay and Bruns, 2014;Vannette et al, 2016;Boeraeve et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Frontiers in Ecology and Evolution | www.frontiersin.org (Heino and Soininen, 2006;Heino and Tolonen, 2018;Rocha et al, 2018;Vilmi et al, 2019) B T (Godon et al, 2016;Moeller et al, 2017) Microbe-Microbe Competition Davison et al, 2015;Lu et al, 2018), B A (Fuhrman et al, 2008;Stomp et al, 2011;Kruk et al, 2012;Sul et al, 2013;Vogt et al, 2019) Okie et al, 2015;Zhou et al, 2016;Xu et al, 2017;Wu et al, 2018) B T (Loudon et al, 2016;Moeller et al, 2017), F T (Peay et al, 2007(Peay et al, , 2010(Peay et al, , 2012Bahram et al, 2013;Vannette et al, 2016;Glassman et al, 2017a,b;Boeraeve et al, 2018), P T (Ishtiaq et al, 2010;Spurgin et al, 2012)A A (Whitaker et al, 2003), B A (Darcy et al, 2018), F T (Li et al, 2020), P A (Soininen et al, 2007;Lepère et al, 2013;Santos et al, 2016) F T (Green et al, 2004) Unknown Mechanism B A (Meador et al, 2009), P A (Soininen and Kokocinski, 2006)…”
Section: Organismal (Physiological)mentioning
confidence: 99%
“…Such low-diversity limitations may reflect both neutral (dispersal) and niche processes (abiotic factors; e.g., [14][15][16][17]). Studies show that longer distances (>10 km) may limit the stochastic dispersal of fungal propagules from one location (native forest) to another (plantation) whereas deterministic traits such as dispersal via spores [14,18] versus mycorrhizal root tips and hyphal networks may operate at finer scales [19][20][21][22]. In addition, biotic (e.g., host nutrient demands, seed dispersal) and abiotic factors (e.g., soil chemistry) may facilitate ECM fungal species with physiological and ecological adaptations depending on the environmental context [23].Recent evidence has demonstrated that phylogenetic distance between exotic and native hosts might explain their (dis)similarities in ECM community composition and richness [24,25].…”
mentioning
confidence: 99%